Predictors of Outcome in Management of Ruptured Arteriovenous Fistula in Hemodialysis Patients: A Cross-Sectional Study at a Tertiary Care Hospital, Karachi: Management of Ruptured Arteriovenous fistula - Basit, Abdul; Masood, Bilal; Memon, Fahad; Habib, Fazal Ameen; Zehra, Dabeeran; Keen, Irfan Tariq (Pakistan Journal of Health Sciences, 2023)
Bleeding from ruptured arteriovenous fistulae (AVF) is a distressing complication resulting from multiple factors and can lead to life-threatening hemorrhage. Objective: To analyze factors that contribute to the development of a bleeding ruptured AVF which could enable us to make decision regarding line of management for saving these AVFs. Methods: This cross-sectional study was conducted at Department of Vascular Surgery, Sindh Institute of Urology and Transplant (SIUT), including 52 patients presenting with burst arteriovenous fistula during the time period of six months. Data collection was carried out using a pretested questionnaire which comprised of detailed history regarding pre-operative and per-operative factors related to burst fistula. Results: The mean age of the patients was 35.7 ± 19.6 years with gender distribution identified as male (51.9%) and female (48.1%). The major outcome of the study was salvageability of AVF which was observed to be 36.5% among the study cohort. We also analyzed association of AVF salvageavility with pre-operative and intraoperative factors which showed its significant association with risk factors such as fistula age (<40 or > 40 days), area of surrounding inflammation, overlying skin, bleeding AVF before initiation of hemodialysis from fistula, type of cannulation, site of bleeding from AVF and ligation/repair status of fistula. Conclusions: Understanding these significantly associated factors could contribute to the early detection and allow measures aimed at averting adverse outcomes, which can span from the loss of vascular access to severe health problems and even, in some cases, prove fatal.